Expression and Secretion of Circular RNAs in the Parasitic Nematode, Ascaris suum - Minkler, Sarah J.; Loghry-Jansen, Hannah J.; Sondjaja, Noelle A.; Kimber, Michael J. (Frontiers in Genetics, 2022)
Circular RNAs (circRNAs) are a recently identified RNA species with emerging functional roles as microRNA (miRNA) and protein sponges, regulators of gene transcription and translation, and modulators of fundamental biological processes including immunoregulation. circRNAs have been found in a variety of species including plants, animals, and model genetic organisms such as the free-living nematode Caenorhabditis elegans. Relevant to this study, circRNAs have recently been described in the parasitic nematode, Haemonchus contortus, suggesting they may have functionally important roles in parasites. Given their involvement in regulating biological processes, a better understanding of their role in parasites could be leveraged for future control efforts. Here, we report the use of next-generation sequencing to identify 1,997 distinct circRNAs expressed in adult female stages of the gastrointestinal parasitic nematode, Ascaris suum. We describe spatial expression in the ovary-enriched and body wall muscle, and also report circRNA presence in extracellular vesicles (EVs) secreted by the parasite into the external environment. Further, we used an in-silico approach to predict that a subset of Ascaris circRNAs bind both endogenous parasite miRNAs as well as human host miRNAs, suggesting they could be functional as both endogenous and exogenous miRNA sponges to alter gene expression. There was not a strong correlation between Ascaris circRNA length and endogenous miRNA interactions, indicating Ascaris circRNAs are enriched for Ascaris miRNA binding sites, but that human miRNAs were predicted form a more thermodynamically stable bond with Ascaris circRNAs. These results suggest that secreted circRNAs could be interacting with host miRNAs at the host-parasite interface and influencing host gene transcription. Lastly, although we have previously found that therapeutically relevant concentrations of the anthelmintic drug ivermectin inhibited EV release from parasitic nematodes, we did not observe a direct effect of ivermectin treatment on Ascaris circRNAs expression or secretion.